2016
DOI: 10.3389/fpls.2016.00498
|View full text |Cite
|
Sign up to set email alerts
|

Phenylacetic Acid Is ISR Determinant Produced by Bacillus fortis IAGS162, Which Involves Extensive Re-modulation in Metabolomics of Tomato to Protect against Fusarium Wilt

Abstract: Bacillus fortis IAGS162 has been previously shown to induce systemic resistance in tomato plants against Fusarium wilt disease. In the first phase of current study, the ISR determinant was isolated from extracellular metabolites of this bacterium. ISR bioassays combined with solvent extraction, column chromatography and GC/MS analysis proved that phenylacetic acid (PAA) was the potential ISR determinant that significantly ameliorated Fusarium wilt disease of tomato at concentrations of 0.1 and 1 mM. In the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 65 publications
0
33
0
1
Order By: Relevance
“…More recently, PAA from Bacillus fortis IAGS162 was shown to be the elicitor of ISR in tomato against F. oxysporum f.sp. lycopersici (Akram et al 2016). Through metabolomics techniques, the PGPR Pseudomonas aeruginosa PM12 was found to promote ISR in tomato challenged with F. oxysporum via 3-hydroxy-5-methoxy benzene methanol (HMB).…”
Section: Diverse Pgpr Molecules Elicit Plant Defensementioning
confidence: 99%
“…More recently, PAA from Bacillus fortis IAGS162 was shown to be the elicitor of ISR in tomato against F. oxysporum f.sp. lycopersici (Akram et al 2016). Through metabolomics techniques, the PGPR Pseudomonas aeruginosa PM12 was found to promote ISR in tomato challenged with F. oxysporum via 3-hydroxy-5-methoxy benzene methanol (HMB).…”
Section: Diverse Pgpr Molecules Elicit Plant Defensementioning
confidence: 99%
“…was the only non-siderophore producing isolate, but it was one of the two strains that produced auxins, and was chosen for this reason. Some authors have shown that auxins are related to the induction of systemic resistance (Akram et al 2016, Petti et al 2012. Three strains, N 10.7 (S. odofirera), N 12.34 (S. rubidaea) and N 11.14 (B. enterophyticus) were chosen with only one biochemical trait, because of their capacity to reduce growth of other strains in plate (data not shown), probably due to the production of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…After 15 days of treatment applications, third true leaves of tomato cultivars were collected for metabolites extraction. Whole metabolite extraction, preparation of the samples and GC-MS analyses were strictly performed as described by Akram et al 23 Chromatograms and mass spectra obtained after GC-MS operation were analyzed through TURBOMASS (Perkin-Elmer). All the biochemicals showing significant changes were enlisted, and a metabolic pathway was plotted.…”
Section: Effect On Plant Metabolismmentioning
confidence: 99%